Bleach. Volume 63, Hear, fear, here - Kubo, Tite; McMurray, Mark (Viz Media San Francisco, CA, 2015)
"Mask De Masculine's onslaught continues as he takes on multiple Soul Reaper captains at once. However, he may have met his match when Renji makes his appearance. Meanwhile, the secrets behind the Quincy king's power may finally be revealed"-- from publisher's web page